Radical empathy as pedagogical praxis: an intersectional feminist approach to building inclusive curriculums and societies - Ahn, Sun Ha (Frontiers in Education, 2025)
From the outset of my doctoral enquiry, a persistent reflexive question has guided my scholarly trajectory: how might educators authentically engage with contexts shaped by intersectional marginalisation—the overlapping and compounding forms of exclusion structured across ethnicity, class, gender, sexuality, age, and health status? This enquiry unfolds through two interrelated domains. First, in my role as a facilitator of qualitative methodology workshops within UK higher education (HE), I have observed discomfort among students when introduced to decolonial perspectives. This resistance often arises not merely from individual reluctance but from deeply entrenched epistemic hierarchies rooted in neoliberal, individualistic, and rationalist ideologies that shape the hidden curriculum. Second, as a critical feminist researcher, I have engaged with the ethical and methodological complexities of working with marginalised participants—specifically, female Black South African women confronting gendered health inequities. These experiences underscore the need to bridge epistemic and affective divides between privileged and marginalised groups in educational settings. This study argues that embedding radical empathy within pedagogical praxis and deliberately integrating intersectional positionalities into curriculum design are vital for cultivating transformative, justice-oriented educational environment. Radical empathy, understood as a sustained ethical–political engagement rather than sentimentality, enables classrooms to function as dialogic and emancipatory spaces where silenced voices are recognised and epistemic comfort is challenged. By reconceptualising classrooms as laboratories of empathy, equity, and democratic renewal, educators can resist market-driven and positivist imperatives, promote critical reflexivity, and cultivate the relational capacities necessary for inclusive, plural, and socially just societies. Although grounded in the UK HE context, the proposed model of pedagogy embedded in radical empathy holds global applicability, offering transferable insights for reimagining education as an emancipatory practice in increasingly divided and commodified academic landscapes.